2004
DOI: 10.17221/4033-pse
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dry matter yield structure of forage grasses

Abstract: An average dry ma�er yield structure (three cuts per growing season) in relation to agronomically valuable characteristics of six forage grass species and a year of herbage utilization was studied over the period of 1989-2002 in Lithuania. The most productive species of the first cut of two years of herbage utilization were Phleum pratense (P < 0.01) and Festulolium hybrids (P < 0.05) (average dry ma�er yield were 7.42 and 6.66 t/ha, respectively), moderately productive -Festuca pratensis, Dactylis glomerata a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
2
17
1
2
Order By: Relevance
“…However, our results were similar to those presented by Akgun et al ( 2008 ). The average plant height in the second cut was 29.9 cm, which is similar to results published by Lemežiene et al ( 2004 ), who reported plant heights in the second cut ranging from 30.2 to 35.9 cm depending on year.…”
Section: Resultssupporting
confidence: 92%
“…However, our results were similar to those presented by Akgun et al ( 2008 ). The average plant height in the second cut was 29.9 cm, which is similar to results published by Lemežiene et al ( 2004 ), who reported plant heights in the second cut ranging from 30.2 to 35.9 cm depending on year.…”
Section: Resultssupporting
confidence: 92%
“…The highest yield was obtained in the first cut, which was conducted at the heading stage. The results were consistent with those obtained in long-term experiments, which indicate that cocksfoot may be harvested at least three times and that the highest biomass yield is obtained from the first cut (Leme ziene et al, 2004). Differences in growth responses to N fertilizer were observed between fertilizers types, especially in later years.…”
supporting
confidence: 88%
“…In the present research, the highest annual biomass yield (10.4 t DM ha −1 ) was obtained in the first year of sward use (at the rate fertilized with digestate at N 450 ). The obtained biomass yield was higher than shown in results achieved in other experiments, where in the first year of sward use cocksfoot fertilized with N 150 produced 7.30 t DM ha −1 (Lemežiene et al., ). On the other hand, in different climate environments, the productivity of cocksfoot is markedly higher.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…are coordinated by adjusting growth, development, cellular and molecular activities (Hubbard 1992(Hubbard , Židonytė 1992. Likewise, timothy (Phleum pratense L.), one of the most productive grass species in terms of first cut yield, forms low aftermath growth under dry conditions (Lemežienė et al 2004). Timothy is valued for its winter hardiness, good palatability, and moderate nutritional feed value and thus is a major forage crop in northern latitudes.…”
Section: Introductionmentioning
confidence: 99%